Scrutinizing Famine Disaster Based On Rainfall Trend Investigation (A Case Study of Khorasan Razavi Province) - Zabihi, Omid; Gheibi, Mohammad; Aghlmand, Reza; Nejatianc, Amir (Journal of Water, 2022)
Rainfall is one of the most important components of the hydrological cycle. The importance of rainfall in arid and semi-arid regions is more apparent. Due to the important role of rainfall trend assessment in the proper management of water resources, in the present study, Khorasan Razavi province, the second-most populous province of Iran located in the northeast of the country, for this purpose was studied. Currently, this region is facing water shortage problems. In this study, the non-parametric Mann-Kendall method was used to evaluate the annual rainfall trend over a thirty-year period from 1989 to 2019. On the other hand, Sen's slope estimator method was used to determine the magnitude of the rainfall trend in the studied synoptic and rain gauge stations. The results showed that the root of water shortage problems is not due to drastic changes in rainfall. Therefore, water shortage problems in Khorasan Razavi province are mainly due to a lack of proper management (i.e., mismanagement). The present study, by examining the rainfall trend using an appropriate framework, tried to take an effective step towards improving the management of water resources in the northeast of Iran.
Keywords: Rainfall; trend analysis; Mann-Kendall test; Sen's slope estimator